Republic of Yemen : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that economic growth in Yemen slowed in 2004 owing to a sharp contraction in the oil sector. Oil production declined by 5.9 percent, reflecting diminishing recovery from aging large oil fields as well as the absence of significant new discoveries. Some progress has been made in structural reforms. The revised General Sales Tax law submitted to parliament in late 2004 included several improvements designed to protect the integrity and simplicity of this tax.